Integration of collaborative medication therapy management in a safety net patient-centered medical home - Moczygemba, Leticia R. (2011)
OBJECTIVE: To describe the integration of collaborative medication therapy management (CMTM) into a safety net patient-centered medical home (PCMH). SETTING: Federally qualified Health Care for the Homeless clinic in Richmond, VA, from October 2008 to June 2010. PRACTICE DESCRIPTION: A CMTM model was developed by pharmacists, physicians, nurse practitioners, and social workers and integrated with a PCMH. CMTM, as delivered, consisted of (1) medication assessment, (2) development of care plan, and (3) follow-up. PRACTICE INNOVATION: CMTM is integrated with the medical and mental health clinics of PCMH in a safety net setting that serves homeless individuals. MAIN OUTCOME MEASURES: Number of patients having a CMTM encounter, number and type of medication-related problems identified for a subset of patients in the mental health and medical clinics, pharmacist recommendations, and acceptance rate of pharmacist recommendations. RESULTS: Since October 2008, 695 patients have had a CMTM encounter. An analysis of 209 patients in the mental health clinic indicated that 425 medication-related problems were identified (2.0/patient). Pharmacists made 452 recommendations to resolve problems, and 384 (85%) pharmacist recommendations were accepted by providers and/or patients. For 40 patients in the medical clinic, 205 medication-related problems were identified (5.1/patient). Pharmacists made 217 recommendations to resolve the problems, and 194 (89%) recommendations were accepted. CONCLUSION: Integrating CMTM with a safety net PCMH was a valuable patient-centered strategy for addressing medication-related problems among homeless individuals. The high acceptance rate of pharmacist recommendations demonstrates the successful integration of pharmacist services.